2018
DOI: 10.1177/0312896218771438
|View full text |Cite
|
Sign up to set email alerts
|

CSR disclosure and financial performance revisited: A cross-country analysis

Abstract: The relationship between corporate social responsibility (CSR) and corporate financial performance (CFP) has been the subject of intensive research. However, limitations with this literature include the use of localised samples, poorly specified control variables and self-constructed CSR disclosure measures that may not represent a firm’s actual CSR performance. Answering the call for ‘better’ CSR research in this field, as well as extending research to a cross-country analysis, this study examines the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
110
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(120 citation statements)
references
References 99 publications
(136 reference statements)
7
110
0
3
Order By: Relevance
“…Wagner () used social indices developed by Waddock and Graves, Ekatah et al () developed key performance indicators for social performance, Sariannidis et al () used nonfarm payroll employment as a social indicator, Ferrero‐Ferrero et al () analyzed the ESG performance of companies, and Beck et al () used Vigeo‐Eiris for CSR and sustainability ratings.…”
Section: Implications For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Wagner () used social indices developed by Waddock and Graves, Ekatah et al () developed key performance indicators for social performance, Sariannidis et al () used nonfarm payroll employment as a social indicator, Ferrero‐Ferrero et al () analyzed the ESG performance of companies, and Beck et al () used Vigeo‐Eiris for CSR and sustainability ratings.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…They found that there is a significant negative short-term impact of CSR adoption and business performance. The CSR-CFP Corporate Financial Performance (CFP) relationship was visited again by several authors (Škare & Golja, 2012;Pätäri, Arminen, Tuppura, & Jantunen, 2014;Vergini, Jacomossi, Turra, & Hein, 2015;Rodriguez-Fernandez, 2016;Carini, Comincioli, Poddi, & Vergalli, 2017;Choongo, 2017;Oh, Hong, & Hwang, 2017;Ang & Weber, 2018;Beck, Frost, & Jones, 2018;Hategan, Sirghi, Curea-Pitorac, & Hategan, 2018;Cherian et al, 2019;Lin, Hung, et al, 2019;Lin, Law, et al, 2019), some of which considered environmental leadership (DiSegni, Huly, & Akron, 2015), its impact on innovation, and firm performance as possible moderating variables (Martinez-Conesa, Soto-Acosta, & Palacios-Manzano, 2017). Ekatah, Samy, Bampton, and Halabi (2011) sought to explore whether CSR is linked to profitability employing simple statistic methods and linear regression.…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…Asian CSR research highlights the contextual issues of the region, such as government power, labour rates, education disparity, and more recently quantifying CSR reporting (Chapple & Moon, 2007;Jain, Keneley, & Thomson, 2015;Kim & Moon, 2015). Within the Australian context, there has been a focus on governance, reporting, stakeholder engagement, and small-to-medium sized organisations (Beck, Frost, & Jones, 2018;Lane & Devin, 2018;Sheedy, 2016;Stewart & Gapp, 2014). Across all regions, including Australia, there is an increasing focus on the role of board diversity and corporate governance (Furlotti, Mazza, Tibiletti, & Triani, 2018;Galbreath, 2011;Manning, Braam, & Reimsbach, 2019;Setó-Pamies, 2015;Uribe-Bohorquez, Martínez-Ferrero, & García-Sánchez, 2018).…”
Section: Corporate Social Responsibility (Csr)mentioning
confidence: 99%
“…First, most previous studies have been evaluated the impact of CSRD activities either internal or external particularly on organizational financial performance (e.g., Bayoud, 2012;Beck, Frost, & Jones, 2018;Eccles, Ioannou, & Serafeim, 2014;Hou, 2018;Rasheed, Arshed, Malik, & Mahmood, 2018;Tang, Hull, & Rothenberg, 2012;Yang & Baasandorj, 2017). First, most previous studies have been evaluated the impact of CSRD activities either internal or external particularly on organizational financial performance (e.g., Bayoud, 2012;Beck, Frost, & Jones, 2018;Eccles, Ioannou, & Serafeim, 2014;Hou, 2018;Rasheed, Arshed, Malik, & Mahmood, 2018;Tang, Hull, & Rothenberg, 2012;Yang & Baasandorj, 2017).…”
mentioning
confidence: 99%
“…The motives to conduct this research are as follows. First, most previous studies have been evaluated the impact of CSRD activities either internal or external particularly on organizational financial performance (e.g., Bayoud, 2012;Beck, Frost, & Jones, 2018;Eccles, Ioannou, & Serafeim, 2014;Hou, 2018;Rasheed, Arshed, Malik, & Mahmood, 2018;Tang, Hull, & Rothenberg, 2012;Yang & Baasandorj, 2017). However, this study attempts to examine the influence of CSRD by adopting both internal and external CSR activities with respect to sales performance that has been ignored in the past.…”
mentioning
confidence: 99%